2021
DOI: 10.1007/s10549-021-06357-7
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and clinical significance of DNA polymerase beta (POLβ) expression in breast ductal carcinoma in situ (DCIS)

Abstract: Background The prediction of clinical behaviour of breast ductal carcinoma in situ (DCIS) and its progression to invasive disease remains a challenge. Alterations of DNA damage repair mechanisms are associated with invasive breast cancer (BC). This study aims to assess the role of base excision repair (BER) DNA Polymerase Beta (POLβ) in DCIS. Methods A cohort of DCIS comprising pure DCIS (n = 776) and DCIS coexisting with invasive BC (n = 239) were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the current study, we provide the first clinical evidence that RECQL loss is a feature of some DCIS which is associated with aggressive phenotype and adverse survival outcomes. We have previously shown that loss of key base excision repair (BER) repair proteins such as XRCC1 [24] or polymerase β [25] in DCIS are also linked with aggressive clinicopathological features and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we provide the first clinical evidence that RECQL loss is a feature of some DCIS which is associated with aggressive phenotype and adverse survival outcomes. We have previously shown that loss of key base excision repair (BER) repair proteins such as XRCC1 [24] or polymerase β [25] in DCIS are also linked with aggressive clinicopathological features and survival.…”
Section: Discussionmentioning
confidence: 99%